Organic products in Central America: current supply and markets: Belize - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
This document is part of a series of studies carried out in all the countries of the region. It deals with the situation in Belize and is divided into five chapters. The first chapter contains general information about the country, while the second describes the main public policies and bodies used to support this sub-sector and the financing situation. Chapter 3 explains the regulations in place and the status of the certification services; Chapter 4 looks at some bodies that support the productive processs and characterizes the producers. The last chapter describes the local market and the status of access to external markets for national products